Znaczenie kultury w dziele ewangelizacji - Miśkowiec, Anna (Annales Missiologici Posnanienses, 2014)
The article focuses on the concept of culture, its etymology, various anthropological interpretations and the way in which the Catholic Church has historically understood the reality of culture. The analysis of evolution of such an understanding culminates in evaluation of the contributions of the 2nd Vatican Council and the consequences of this development for the missionary involvement of the Church. While the Church is historically related to concrete cultural contexts, the Gospel is not limited to any of those contexts. The main challenge of the missionary work is to set up fruitful relations with the local cultures in order to establish mutual relations between the Gospel and cultural values.